Scholae Academicae Some Account of the Studies at the English Universities in the Eighteenth Century - Wordsworth, Christopher (Cambridge library collection. Cambridge, 1877)
Christopher Wordsworth (1848–1938), was a great-nephew of the poet, and part of a Victorian dynasty of Cambridge academics. In this book, published in 1877, he describes the state of the English universities in the eighteenth and early nineteenth centuries, before the reforms following the 1852 Royal Commission. He reviews the historic areas of study from the arts and mathematics to the 'trivials' - grammar, logic and rhetoric - and discusses the introduction of more recent disciplines such as physics, anatomy, chemistry, mineralogy and botany. His stated aim is to preserve an account of 'the methods and processes of University Study through which were educated the minds which have done so much to make our University and our Country what they are'. A companion volume, Wordsworth's Social Life at the English Universities in the Eighteenth Century is also reissued in the Cambridge Library Collection